Stimulation of d - and l -lactate dehydrogenases transcriptional levels in presence of diammonium hydrogen phosphate resulting to enhanced lactic acid production by Lactobacillus strain - Singhvi, Mamata S.; Zendo, Takeshi; Iida, Hiroshi; Gokhale, Digambar V.; Sonomoto, Kenji (Journal of Bioscience and Bioengineering, 2017)
The present study revealed the effect of nitrogen sources on lactic acid production and stimulation of d- and l-lactate dehydrogenases (LDH) of parent Lactobacillus lactis NCIM 2368 and its mutant RM2-24 generated after UV mutagenesis. Both the parent and mutant strains were evaluated for d-lactic acid production in control and modified media. The modified media did not show remarkable effect on lactic acid production in case of parent whereas mutant exhibited significant enhancement in d-lactic acid production along with the appearance of l-lactic acid in the broth. Both LDH activities and specific activities were found to be higher in mutant than the parent strain. These results suggested that the diammonium hydrogen phosphate in modified media triggered the expression of LDH genes leading to enhanced lactic acid production. This observation has been proved by studying the expression levels of d- and l-LDH genes of parent and mutant in control and modified media using quantitative RT-PCR technique. In case of mutant, the transcriptional levels of d-LDH and l-LDH increased ∼17 fold and ∼1.38 fold respectively in modified medium compared to the values obtained with control medium. In case of parent, no significant change in transcriptional levels of d- and l-LDH was found when the cells were grown in either control medium or modified medium. This study suggested that the mutant, RM2-24 has l-LDH gene which is expressed in presence of (NH4)2HPO4 resulting in l-lactic acid production. Co-production of l-lactic acid in d-lactic acid fermentation may be detrimental in the PLA production.

Greener L-lactic acid production through in situ extractive fermentation by an acid-tolerant Lactobacillus strain - Singhvi, Mamata S.; Zendo, Takeshi; Gokhale, Digambar; Sonomoto, Kenji (Applied Microbiology and Biotechnology, 2018)
Lactic acid (LA) fermentation requires a neutralizer for a physiologically acceptable range. However, a neutralizer generates a large amount of gypsum, an environmental pollutant. Furthermore, the downstream processing is complicated and expensive, comprising 50–70% of the total cost. We previously developed a Lactobacillus delbrueckii FM1, which can produce undissociated LA without neutralizer. Here, we improved FM1 by adaptive evolution at pH 4.5, which generated Adp FM1 showing an ~ 1.80-fold increase in LA production compared to FM1. The LA production via fed-batch fermentation yielded 36.2 g/L of LA, with a productivity of 0.500 g/L/h. However, cell viability was reduced due to the acidic pH and/or end-product inhibition. Therefore, an in situ LA recovery process using an extractive solvent was employed to maintain cell viability. Adp FM1 produced 49.2 g/L of LA via in situ LA-extractive fed-batch fermentation, which was ~ 1.4-fold higher than that without LA extraction. Adp FM1 provided a total LA productivity of 0.512 g/L/h in 96 h. Among the tested strains, Adp FM1 exhibited the highest H⁺-ATPase activity and a 415-fold increase in H⁺-ATPase gene expression compared to the parent strain. These results suggest that the in situ LA extractive fermentation process will ease downstream processing and prove to be a more economical and environmentally friendly option compared to the present fermentation. To our knowledge, this is the first report on the production of undissociated L-LA by Lactobacillus using an in situ recovery process, with high LA production levels and productivity.